A review of Moroccan medicinal plants used in the treatment of inflammation - Aziz ZOUHRI; Yahya EL-MERNISSI; Naoual EL MENYIY; Toufik BOUDDINE; Nora MIR; Kamal EL AISSAOUI; Hassan AMHAMDI; Abdelhay ELHARRAK; Lhoussain HAJJI (Notulae Scientia Biologicae, 2023)
Inflammation is a mechanism that occurs against aggressive agents such as infections, wounds, pollens, autoimmune diseases, and tissue damage. Morocco has traditionally used herbal remedies to treat many illnesses, including inflammation. The objective of this study was to describe the Moroccan medicinal plants used in inflammation treatment. This systematic review examines ethnobotanical studies published in English and French in the literature as well as the pharmacological studies that assess anti-inflammatory activity in vitro and in vivo, from databases (Scopus, Web of Science, Science Direct, and Springer). The research was carried out until August 2021. In ethnobotanical surveys, 100 medicinal plants were identified, which belonged to 52 families of which the most often cited are Lamiaceae with 18 species, followed by Apiaceae (13 species) and Asteraceae (10 species). The most used plants to treat inflammation in Morocco are: Coriandrum sativum L, Caralluma europaea (Guss.) Nebr., Opuntia ficus-indica (L.) Mill., Capparis spinosa L., Anacyclus pyrethrum (L.) Lag, Ajuga iva (L.) Schreb., Thymus atlanticus (Ball) Pau, Thymus saturejoides Coss, Thymus zygis L., Lawsonia isermis L. and Rosmarinus officinalis L. This review highlighted Moroccan medicinal plants used in traditional medicine to treat inflammation. Many of this plant species require additional pharmacological, and clinical studies to verify which plants are effective in treating inflammation.